ANALYSIS OF INTERNAL FACTORS THAT IMPACT THE COMPANY'S DECISION TO REVALUE ASSETS IN INDONESIA - Lita Natalia; Elis Mediawati (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study investigates the internal factors influencing companies' decisions to revalue assets in Indonesia through a systematic literature review. Examining 20 relevant research articles, the research identifies key factors and their impact. Findings reveal that operating cash flow positively influences asset revaluation, enhancing asset valuation and liquidity. Fixed asset intensity, ownership structure, and leverage also play crucial roles. Larger firms with substantial debt are more likely to revalue assets, benefiting from improved financial ratios and creditor confidence. The military background of board members correlates with a preference for asset revaluation, potentially attracting funds and investors. Additionally, firms with lower market-to-book ratios tend to revalue assets to enhance financial performance, aligning with positive accounting theory. The study contributes valuable insights into the factors guiding asset revaluation decisions in Indonesia, providing a foundation for future research in this area.